HARRY POTTER: A MODERN MAGE HERO - Pádua, Érika de (Em Tese, 2005)
J. K. Rowling’s Harry Potter series follows the tradition of fantasy works such as Tolkien’s The Lord of the Rings. An important difference from these, however, is that it showsthe contemporary mage looking for answers for fundamental existential questions of identity.